A Radiological Sign in Chronic Collateral Ligament Injuries of the Thumb Metacarpophalangeal Joint. (June 2013) - Hunter, Alistair R.; Tansey, Rosamond J.; Muir, Lindsay T.
Background: Differentiating chronic from acute injuries of the collateral ligament of the metacarpophalangeal joint (MCPJ) of the thumb can be difficult in the absence of a conclusive history and examination. We aimed to establish the presence of a radiological sign in patients with a chronic injury and the reliability of the sign in differentiating chronic from acute ligament injury. Method: Consecutive patients undergoing surgical treatment for chronic ( n =14) or acute ( n =8) ligament injury of the MCPJ of the thumb were identified retrospectively. Six upper limb orthopedic surgeons and four musculoskeletal radiologists were recruited from three regional centers. Observers judged the presence or absence of the sign, an exostosis at the level of the neck of the thumb metacarpal, on radiographs presented on a computer program. The radiographs were then observed in a different random order. The sensitivity, specificity, positive predictive value (PPV), and negative predictive values (NPV) of the radiological sign were evaluated for each observer and the intra- and interobserver error was calculated. Results: The mean observer specificity and sensitivity for the sign were 84 and 54 %, respectively. The PPV and NPV were 89 and 52 %, respectively. The kappa statistic for intraobserver error was 0.69 and interobserver error 0.34. Conclusions A radiological sign associated with chronic collateral ligament injuries of the MCPJ of the thumb is established. The presence of the sign can increase the confidence of the clinician in differentiating chronic from acute collateral ligament injuries, when history and examination are inconclusive in this respect.